Synergistic Effect of 1-MCP Fumigated with Chitosan Coating on Shelf-life and Physico-Chemical Quality of Marian Plum (Bouea macrophylla) Fruit - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2020)
Marian plum fruit has high nutritional and functional components which are beneficial for human health. However it has a short shelf-life owing to its high respiration and ethylene production. 1-methylcyclopropene is an inhibitor of ethylene action even at low concentration to hinder ripening and improving storage stability on variety of fruits. Chitosan has strong antimicrobial and antifungal properties that could effectively adjust the permeability of gas exchange, slow down respiration rate, hinder fruit decay. Objective of this study focused on the evaluation of 1-MCP fumigation at different levels (20 ppm, 40 ppm, 60 ppm, 80ppm, 100 ppm) in combination with chitosan coating (0.1%, 0.15%, 0.2%, 0.25%, 0.3%) on shelf-life and quality of marian plum during 14 days of storage at ambient temperature. Our findings will provide better insights for manufacturers in postharvest management.Keywords: Marian plum, Chitosan, 1-MCP, Fumigation, Coating, Posthavest